Use of autologous bone marrow stem cell implantation for osteonecrosis of the knee in sickle cell disease: a preliminary report - Daltro, Gildasio (BMC Musculoskelet Disord, 2018)
BACKGROUND: The purpose of our study was to evaluate safety, feasibility and clinical results of bone marrow mononuclear cell (BMC) implantation for early-stage osteonecrosis of the knee (OK) secondary to sickle cell disease. METHODS: Thirty-three SCD patients (45 knees) with OK treated with BMC implantation in the osteonecrotic lesion were clinically and functionally evaluated through the American Knee Society Clinical Score (KSS), Knee Functional Score (KFS) and Numeric Rating Scale (NRS) pain score. MRI and radiographic examinations of the knee were assessed during a period of five years after intervention. RESULTS: No complications or serious adverse event were associated with BMC implantation. From preoperative assessment to the latest follow-up, there was a significant (p < 0.001) improvement of clinical KSS (64.3 ± 9.7, range: 45–80 and 2.2 ± 4.1, range: 84–100, respectively), KFS (44.5 ± 8.0, range: 30–55 and 91.6 ± 5.8, range: 80–100, respectively) and reduction of NRS pain score (6.7 ± 1.2, range: 4–9 and 3.4 ± 1.0, range: 2–5, respectively). In total, 87% of patients (29/33) consistently experienced improvements in joint function and activity level as compared to preoperative score. No patient had additional surgery following BMC implantation. Radiographic assessment showed joint preservation and no progression to subchondral collapse at most recent follow-up. CONCLUSIONS: The technique of BMC implantation is a promising, relatively simple and safe procedure for OK in SCD patients. Larger and long-term controlled trials are needed to support its clinical effectiveness. TRIAL REGISTRATION: ClinicalTrials.gov NCT02448121. Retrospectively registered 19 May 2015.